2013
DOI: 10.1038/pr.2013.216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity intervention programs on adipokines, insulin resistance, lipid profile, and low-grade inflammation in 3- to 5-y-old children

Abstract: Background: Childhood obesity can cause the development of cardiovascular risk factors. We assessed the effect of a multidisciplinary intervention program on cardiovascular risk factors and compared this effect with a usual-care program in 3-to 5-y-old overweight or obese children. Methods: Seventy-five children were randomly assigned to a multidisciplinary intervention or a usual-care program. Anthropometry, body composition, and abdominal adipose tissue were assessed at the start and end of a 16-wk program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…Obesity has been associated with lowgrade chronic inflammation, which is mediated by increased inflammatory markers such as IL-6 [53,54]. A reduction in the inflammatory state of obese subjects has been reported after dietary programs [55,56]. In this sense, we expected that, after the weight loss induced in the ER group, the IL-6 decreased, which would be in agreement with its higher methylation levels.…”
Section: Discussionsupporting
confidence: 63%
“…Obesity has been associated with lowgrade chronic inflammation, which is mediated by increased inflammatory markers such as IL-6 [53,54]. A reduction in the inflammatory state of obese subjects has been reported after dietary programs [55,56]. In this sense, we expected that, after the weight loss induced in the ER group, the IL-6 decreased, which would be in agreement with its higher methylation levels.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, some authors report no association with anthropometric changes in PP individuals, as well as no correlation with changes in lipid profile and in IR [104].…”
Section: Interventional Studies and Adiponectin Levelsmentioning
confidence: 99%
“…In addition, a recent study has shown that pre‐pubertal insulin‐glucose metabolism is associated with adult CVD risk and markers of atherosclerosis . Reduced hs‐CRP inflammation markers have also been reported in previous lifestyle interventions in children with obesity …”
Section: Discussionmentioning
confidence: 94%